1979
DOI: 10.1515/zna-1979-0211
|View full text |Cite
|
Sign up to set email alerts
|

Crystalline Oxide Solid Solutions in Oxygen Potential Gradients

Abstract: The steady state demixing of an initially homogeneous oxide solid solution (A, B)0 in an oxygen potential field is studied theoretically and experimentally.In case that D\ > DB Do > the crystal is shifted with respect to the oxide lattice system toward the higher oxygen potential and is enriched in A at the side of the higher oxygen potential, while the transport of oxygen in the crystal is negligible. A numerical solution of the transport problem is presented, and the predicted effect is verified experimental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

1989
1989
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(32 citation statements)
references
References 5 publications
1
31
0
Order By: Relevance
“…Although, cation diffusivities are normally several orders of magnitude lower than that of oxygen ions [21], at sufficiently long times, high temperatures [22], and electric fields [23][24][25], substantial cation migration may still occur. Note that the migration of the different cations are not identical; certain elements migrate faster, others slower [26]. We can expect the appropriate gradient terms and concentration changes to be appreciable over a region of about 1 lm from the interface [27], consistent with the experimental results.…”
Section: Discussionsupporting
confidence: 81%
“…Although, cation diffusivities are normally several orders of magnitude lower than that of oxygen ions [21], at sufficiently long times, high temperatures [22], and electric fields [23][24][25], substantial cation migration may still occur. Note that the migration of the different cations are not identical; certain elements migrate faster, others slower [26]. We can expect the appropriate gradient terms and concentration changes to be appreciable over a region of about 1 lm from the interface [27], consistent with the experimental results.…”
Section: Discussionsupporting
confidence: 81%
“…The phenomenon of kinetic demixing was first analyzed by Schmalzried et al [7] and experimentally demonstrated using as a model system the oxide solid solution (Co 1-x Mg x )O, where Co is the faster component. As expected, strong enrichment of Co was found at the high-p O 2 side of the material.…”
Section: Demixing Of Oxides In An Oxygen Potential Gradientmentioning
confidence: 99%
“…8), whereas in the latter case, the cross-coefficients have to be considered. [7], the demixing profile is then obtained by integration of eq. 11 with appropriate boundary conditions.…”
Section: Steady-state Demixing In An Oxygen Potential Gradientmentioning
confidence: 99%
“…Under working conditions, these materials are often exposed to external forces causing both reactions and transport within the materials. Prominent examples are electromigration or kinetic demixing in electric fields [1][2][3][4][5], kinetic demixing in chemical potential gradients [6][7][8][9], stress-driven segregation [10,11] or thermodiffusion ( [12][13][14][15][16][17][18][19][20], see [21,22] for reviews).…”
Section: Introductionmentioning
confidence: 99%